2020
DOI: 10.1108/gkmc-10-2019-0122
|View full text |Cite
|
Sign up to set email alerts
|

An integrated understanding of academics knowledge sharing behaviour

Abstract: Purpose The purpose of this study is to examine the underlying functions of sense of spirituality (SS), emotional intelligence (EI) and perceived work environment (PWE) towards knowledge sharing behaviour (KSB) among the academic staff of higher learning institutions (HLIs) through a comparative investigation. This study extends the investigation by examining the relationship between SS and KSB through the mediating role of EI. The moderating role of PWE between SS and KSB was also tested. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Competitive advantage is the product of effective management and utilisation for the “difficult to duplicate” knowledge assets (Chong et al , 2009). Accordingly, most organisations have started to give more attention to knowledge creation, sharing and application within their organisations (Abdelrahman, 2013; Jones, 2006; Rahman et al , 2020); in particular, in promoting organisations innovativeness (Al-Dmour et al , 2020; Naqshbandi and Jasimuddin, 2018). Nowadays, organisations should give more attention to knowledge sharing amongst employees.…”
Section: Introductionmentioning
confidence: 99%
“…Competitive advantage is the product of effective management and utilisation for the “difficult to duplicate” knowledge assets (Chong et al , 2009). Accordingly, most organisations have started to give more attention to knowledge creation, sharing and application within their organisations (Abdelrahman, 2013; Jones, 2006; Rahman et al , 2020); in particular, in promoting organisations innovativeness (Al-Dmour et al , 2020; Naqshbandi and Jasimuddin, 2018). Nowadays, organisations should give more attention to knowledge sharing amongst employees.…”
Section: Introductionmentioning
confidence: 99%
“…Adhikari et al (2020) suggested that the planned dissemination of information through trusted sources with clear and reliable messages constitutes an influential defensive role in mitigating the perceived risk among potentially affected people. Researchers elucidated that the way people perceive risk may not firmly represent the absolute risk associated with the pandemic outbreak (Bavel et al , 2020; He et al , 2020; McKibbin and Fernando, 2020; Nicomedes and Avila, 2020; Rahman et al , 2020). The overstatement of perceived risk among people often occurs because of unclear information or the misuse of social media (Jain and Kumar, 2015; La et al , 2020; Yasir et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parallel to this, the better knowledge or education acquired about the pandemic, the better stimulation toward prevention commitment (Bakhtiari et al , 2020; Gambhir et al , 2016; Nemati et al , 2020; Rahman et al , 2020). Meanwhile, many researchers found that the attitude of knowledgeable individuals on viral transmission modes and measures of prevention differ notably in comparison to unaware people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, employees benefit from team effectiveness and individual learning (Lin et al , 2020). However, a perceived work environment is responsible for knowledge sharing behavior among the employees (Rahman et al , 2020). Knowledge sharing can be possible when there is a presence of trust among the employees.…”
Section: Research Literaturementioning
confidence: 99%